Evaluation of software quality attributes for vessel tracking management system (VTMS) - Zulzalil, Hazura; Talha, Hazliana; Sharif, Khaironi Yatim (School of Computing, Universiti Utara Malaysia, 2015)
Software quality and assurance becomes inevitable as the non-functional requirements continue to gain more popularity than functional requirements. Even some system could resolve some problem, but if non-functional requirements been neglected, at that point the solution may be impractical. The system with least features and quality characteristics will lead to low demand and failed-to-market. The aim of this study was to evaluate the quality in use attributes for Vessel Tracking and Management System (VTMS) adopted from the latest ISO/IEC 25010 quality model in the perspective of users’ satisfaction. Five properties of quality in use are explicitly evaluated which are effectiveness, efficiency, satisfaction, freedom from risk and context coverage. A study was conducted through observation and survey to evaluate all five quality in use attributes of VTMS and to explore the relationship between each quality in use attribute to determine the overall users’ satisfaction. Generally, this study provides an early empirical evaluation of the practical value of case study method. Firstly, from the VTMS perspective, the system provide a great 100% in functions coverage (completeness) although there are two (2) functions need to take immediate action in terms of accuracy so make up total 98.4% for effectiveness. On the other hand, the efficiency which measure the response time for each VTMS main tasks was 92.83%. It is concluded that all five (5) quality in use attributes scores more than 75% which are above the MMEA’s minimum requirement on overall users’ satisfaction.